Brief communication: Grease Ice in the Antarctic Marginal Ice Zone - Paul, Felix; Mielke, Tommy; Nisters, Carina; Schröder, Jörg; Rampai, Tokoloho; Skatulla, Sebastian; Audh, Riesna; Hepworth, Ehlke; Vichi, Marcello; Lupascu, Doru C. (2021)
Frazil ice, consisting of loose disc-shaped ice crystals, is the very first ice that forms in the annual cycle in the marginal ice zone (MIZ) of the Antarctic. A sufficient number of frazil ice crystals forms the surface <q>grease ice</q> layer taking a fundamental role in the freezing processes in the MIZ. As soon as the ocean waves are sufficiently damped, a closed ice cover can form. In this brief communication we investigate the rheological properties of frazil ice, which has a crucial influence on the growth of sea ice in the MIZ. Grease ice shows shear thinning flow behavior.